2020
DOI: 10.1590/0104-530x3772-20
|View full text |Cite
|
Sign up to set email alerts
|

Project management in public-private partnerships: a conceptual framework based on a systematic literature review

Abstract: Despite the increasing number of Public-Private Partnerships projects, the results have shown little effectiveness and difficulties in several aspects of project management. This study performs a systematic literature review combining bibliometric analysis and content analysis to identify the challenges in managing these projects and techniques to overcome them, highlighting the critical success factors for project management. The results indicate an increasing number of researches in the field, but there is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
0
1
0
Order By: Relevance
“…A preliminary assessment of this list shows that the majority of this type of review study has put emphasis on urban development and planning, water treatment, risk allocation and management, and sustainability. In fact, few studies have directed efforts toward holistic analysis of PPP, which can be found in Roehrich et al [30], Xiong et al [31], Zhang et al [32], and Magalhães et al [33].…”
Section: Former Literature Review Studies Using Bibliometric Analysismentioning
confidence: 99%
“…A preliminary assessment of this list shows that the majority of this type of review study has put emphasis on urban development and planning, water treatment, risk allocation and management, and sustainability. In fact, few studies have directed efforts toward holistic analysis of PPP, which can be found in Roehrich et al [30], Xiong et al [31], Zhang et al [32], and Magalhães et al [33].…”
Section: Former Literature Review Studies Using Bibliometric Analysismentioning
confidence: 99%
“…One of the biggest challenges for organizations is the project team's commitment to project management. At the beginning of project management, it was possible to execute successful projects, only defining time and costs (Thamhain, 1993;Magalhães et al, 2020). However, it is currently observed that this is not enough for the success of a project.…”
Section: Introductionmentioning
confidence: 99%